Pengaruh Sikap Belajar Siswa terhadap Kemampuan Pemahaman Konsep Matematis - Yarmayani, Ayu (Universitas Batanghari Jambi, 2025)
This study aims to determine the learning attitudes towards the mathematical concept comprehension ability of seventh-grade students of SMPIT Asy-Syifa. This study uses a quantitative approach using a simple linear regression test. Data collection was carried out by administering questionnaires and tests on mathematical concept comprehension abilities. Data analysis techniques used are product moment correlation, significance test and determinant coefficient. The results of this study indicate that there is a positive and significant influence between learning attitudes and the mathematical concept comprehension ability of seventh-grade students of SMPIT Asy-Syifa.